Does Domain of Absolute Value Function Always Positive? Commognitive-Conflict Analysis of Students of First Semester - Emanuel, Endrayana Putut Laksminto; Nusantara, Toto; Rahardi, Rustanto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to analyze the result of students' work in finding the solution to math-problems about absolute functions. Commognitive's analysis was used to analyze student works in this qualitative research. This research's methods were, namely, preparing, collecting data, transcription data, and analyzing data. A total of 25 students from two universities were given math questions, and two were selected as research subjects. The selection of subjects is based on different and exciting work results. The research subjects attended in-depth interviews to learn more about the commognitive's components. The results showed that commognitive conflict occurred in the word use component when the subject experienced errors in interpreting the data on the questions. Subjects cannot correctly describe the graphic requested in the questions (visual mediators). Describing what is known in the problem is also incompatible (narratives). Subjects experienced the incorrect routines. Based on the results of in-depth interviews, it can be said that the commognitive conflicts occurred because of a lack of understanding of the concepts.